2020
DOI: 10.1039/c9ew00931k
|View full text |Cite
|
Sign up to set email alerts
|

Selective removal of natural organic matter during drinking water production changes the composition of disinfection by-products

Abstract: Disinfection by-products (DBPs) are potentially toxic compounds formed upon chemical disinfection of drinking water. This study evaluate how treatment approaches affect DBP formation and composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…1), was executed to further validate the presence of halogenated compounds in the natural samples. While suspicious halogens could be eliminated by the optional precursor inspection rule (i.e., Filter Rule 3), the identification of Cl-halogens can be affected by Cl-adduct ions potentially formed during the ESI negative mode ionization via interaction of DOM molecules and remaining Clfrom the SPE-extraction using HCl 27 . In this study, the potential adduct of Cl-molecules were observed for the SPE-extracted SRNOM and NRNOM, while not for the SPE-extracted SRFAII (Fig.…”
Section: Freshwater Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…1), was executed to further validate the presence of halogenated compounds in the natural samples. While suspicious halogens could be eliminated by the optional precursor inspection rule (i.e., Filter Rule 3), the identification of Cl-halogens can be affected by Cl-adduct ions potentially formed during the ESI negative mode ionization via interaction of DOM molecules and remaining Clfrom the SPE-extraction using HCl 27 . In this study, the potential adduct of Cl-molecules were observed for the SPE-extracted SRNOM and NRNOM, while not for the SPE-extracted SRFAII (Fig.…”
Section: Freshwater Samplesmentioning
confidence: 99%
“…These results suggest that the formation of Cl-DOM adducts is controlled not only by the presence of remaining Cl -, but also by the types of DOM. In order to avoid adduct formation, formic acid has been suggested in the SPE extraction instead of HCl [16][17][18]27,28 . However, the employment of other type of acid, formic acid, in SPE extraction (instead of HCl) may lead to the occurrence of formate adduct ions in ESI negative mode [29][30][31] , interfering the formula assignment of nonhalogenated DOM molecules.…”
Section: Freshwater Samplesmentioning
confidence: 99%
“…While suspicious halogens could be eliminated by the optional precursor inspection rule (i.e., Filter Rule 3), the identification of Cl-halogens can be affected by Cl-adduct ions potentially formed during the ESI negative mode ionization via interaction of DOM molecules and remaining Clfrom the SPE-extraction using HCl 27 . In this study, the potential adduct of Cl-molecules were observed for the SPE-extracted SRNOM and NRNOM, while not for the SPE-extracted SRFAII (Fig.…”
Section: Freshwater Samplesmentioning
confidence: 99%
“…The presence of DBPs is a prominent concern for municipal treatment facilities ( AWWA, 2020 ), but formation can be mitigated through a variety of approaches that target additional removal of dissolved organic carbon or with the adoption of alternative disinfection processes. While prior studies have focused on DBP reduction by changing conventional unit processes during drinking water treatment ( Andersson et al., 2020 ; Postigo et al., 2021 ; Zhang et al., 2021 ), those methods present an additional economic and infrastructure burden that can be particularly pronounced for smaller facilities. In addition, disinfection methods that use alternatives to chlorine can form other, less understood byproducts ( Richardson and Plewa, 2020 ).…”
Section: Introductionmentioning
confidence: 99%